2012
DOI: 10.3109/0886022x.2012.700886
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Angiotensin II Receptor 1 (AT1) Blockade in Cisplatin-Induced Nephrotoxicity in Rats: Gender-Related Differences

Abstract: It is documented that chronic renal diseases are gender related. The protective role of angiotensin II receptor 1 (AT1) blocker losartan against cisplatin (CP)-induced nephrotoxicity was reported in males, but the role of gender is not well known. Six groups of Wistar rats were studied. Rats were divided into two groups of males and females to receive losartan for 9 days plus a single dose of CP (7 mg/kg) at day 3. Two positive control groups of males and females received the same regimen, except that they rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
65
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 34 publications
10
65
1
Order By: Relevance
“…Inflammation, oxidative stress, and change in the renal circulation may also be induced by CDDP [46]. To decline CDDP-induced nephrotoxicity, recent studies have concentrated on many supplementations [711]. Losartan is an angiotensin type-1 receptor blocker as well as an antioxidant, which has been suggested to be nephroprotective against CDDP-induced nephrotoxicity by others [10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation, oxidative stress, and change in the renal circulation may also be induced by CDDP [46]. To decline CDDP-induced nephrotoxicity, recent studies have concentrated on many supplementations [711]. Losartan is an angiotensin type-1 receptor blocker as well as an antioxidant, which has been suggested to be nephroprotective against CDDP-induced nephrotoxicity by others [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…To decline CDDP-induced nephrotoxicity, recent studies have concentrated on many supplementations [711]. Losartan is an angiotensin type-1 receptor blocker as well as an antioxidant, which has been suggested to be nephroprotective against CDDP-induced nephrotoxicity by others [10, 11]. Losartan may reduce renal disease progression in patients with type 2 diabetes [12] and decrease hypertension [13] and microalbuminuria or proteinuria [14, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the damaged kidneys gain weight, and the serum creatinine level increases as the damage increases. [30][31][32][33][34] Therefore, the renal effects of PTX solution, PS, or PSC were examined by determining the kidney weights and serum creatinine levels. The normalized kidney weight after treatment with PTX solution was 4.87±0.35 mg/g, significantly (1.35-fold) higher than that of nontreated kidney ( Figure 5A).…”
Section: Evaluation Of Nephrotoxicitymentioning
confidence: 99%
“…3 In another study, we observed that losartan as an angiotensin receptor blocker could attenuate cisplatin kidney toxicity in male rats, while it aggravates the cisplatin kidney injury in female rats. 4 We concluded that gender difference of cisplatin renal toxicity was related to the reninangiotensin system receptors in the kidneys. [4][5][6][7][8][9] Moreover, we recently found that vitamin C, vitamin E, or losartan have no ameliorative effects against cisplatin-kidney toxicity in presence of estrogen in ovariectomized rat model of cisplatin toxicity, 10 which is in agreement with our previous findings too.…”
mentioning
confidence: 99%